Assessing stakeholder perceptions of the american society for biochemistry and molecular biology accreditation program for baccalaureate degrees. Issue 5 (26th October 2018) - Dean, Diane M.; Martin, Debra; Carastro, L. Michael; Kennelly, Peter J.; Provost, Joseph J.; Tansey, John T.; Wolfson, Adele J.
Abstract: The American Society for Biochemistry and Molecular Biology (ASBMB) began an accreditation program in 2013. The criteria for accreditation of undergraduate programs include sufficient infrastructure ‐ number and expertise of faculty, physical space and equipment, support for faculty and students ‐ and incorporation of core concepts in the curriculum ‐ structure and function of biomolecules; information storage; energy transfer; and quantitative skills. Students in accredited programs are able to have their degrees ASBMB certified by taking an exam focused on knowledge or skills across the four core concept areas. Members of the accreditation committees administered a survey to key stakeholders in the BMB community: undergraduate programs, both those that have applied for accreditation and those that have not; alumni/ae of accredited programs; graduate and professional programs; and employers. The goals of the study were to gauge the success of the program and determine necessary areas of improvement. The results indicate that the major benefits of applying for accreditation are the impetus to gather data and analysis not generally collected, and access to assessment data via the exam. However, stakeholders outside of the undergraduate community showed little awareness of the accreditation program. Additionally, the application process itself was seen to be very time consuming. This feedback will be used to improve the process and engage in further outreach. © 2018 International Union of Biochemistry and Molecular Biology, 46(5):464–471, 2018.